Sense of Community dan Wellness pada Mahasiswa (Studi pada Universitas Muhammadiyah Sidoarjo) - Widyastuti Widyastuti; Effy Wardati Maryam (Lembaga Publikasi Ilmiah dan Penerbitan (LPIP), 2019)
Student wellness is one of the keys to success in Higher Education. Community is a potential psychological resource in maintaining wellness within the students. Sense of community is related to the wellness of the students. This study aims to determine the relationship between wellness and sense of community in students of Muhammadiyah University of Sidoarjo (UMSIDA). A total of 66 students were included as respondents in this study obtained by using cluster sampling technique. The data were collected using Wellness Evaluation of Lifestyle inventory and Sense of Community Scale. The data analysis used is Pearson's correlational analysis. The result, there is a significant relationship between sense of community and wellness in UMSIDA students. That is, students with the SoC have more opportunities to achieve wellness better than other who doesn’t.